Stadium Coverage Using Directional Antennas for High Density Access Points Based on Narrow HPBW - Hasdi Radiles; Sutoyo Sutoyo; Dio Alam Pratama; Ahmad Faizal (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2023)
The existence of a Wi-Fi network in the stadium is an important issue because of the many requests for communication access from spectators. Implementation of HD-AP Wi-Fi using directional antennas is one solution to avoid severe interference. This study simulates the coverage of the AP installed on the roof of the tribune station. The simulator is designed using HPBW Elevations 200, 400 and 600. Testing also considers the use of the appropriate transmit power, to obtain the appropriate HPBW combination to avoid interference. The analysis is carried out by comparing the reception of the strongest signal with reception at the sector border. The results of the study show that Antenna directional with HPBW Elevation 400 is more effective in serving users in three service sectors.